Application of different fruit peels powder as an organic fertilisers for the effective growth of water spinach (Ipomoea aquatica) - Nashrin Iszhan, Ishak; Nazikussabah, Zaharudin; Farah Nurshahidah, Mohd Subakir; Hew, Kar Mun; Teo, Hui Thing (Trans Tech Publications Ltd, Switzerland, 2021)
Macronutrients such as nitrogen (N), phosphorus (P) and potassium (K) are usually found in fertilizers which is essential to plant growth and development. The study reports on the utilization of different fruit peels as an organic fertilizer for the effective growth of water spinach (Ipomoea Aquatica). Each fruit peels of pineamle, banana and mango were collected separately from local fruit vendors. The fruit peels were cleaned, dried, and then grinded into powder individually. The chemical composition of fruit peels powder was analysed by Inductively Coupled Plasma-Optical Emission Spectrometry (ICP-OES) and CHNOS analyser which NPK concentration was determined. Among three analysed fruit peels, results demonstrated that banana peels powder showed the highest concentration of K and N, which consists of 26557.86 mg/L and 1.61%, respectively. Besides that, electrical conductivity measurement and water absorption capacity of fruit peels powder was studied. Plants were grown under vary amount of fruit peels powder treatments (mango, banana, and pineapple peels application), as well as control treatments (no fertilizer application). Plant height and number of leaves per plant were analysed to investigate the effect of fruit peels powder treatment on plant growth. The application of 3 g pineapple peels powder gave the better performances in all water spinach growth parameters with mean maximum plant height of 20.83±3.01 cm, number of leaves per plant of 9 was recorded. Hence, it can be concluded that 3 g pineapple peels powder can efficiently improve the utilization efficiency of fertilizers in agricultural production.